Out of my head : on the trail of consciousness - Parks, Tim (New York Review book., 2018)
"Hardly a day goes by without some discussion about whether computers can be conscious, whether our universe is some kind of simulation, whether the mind is a unique quality of human beings or is spread out across the universe like butter on bread. Most philosophers believe that our experience is locked inside our skulls, an unreliable representation of a quite different reality outside. Color, smell, and sound, they tell us, occur only in our heads. Yet when neuroscientists look inside our brains to see what's going on, they find only billions of neurons exchanging electrical impulses and releasing chemical substances. Five years ago, in a chance conversation, Tim Parks came across a radical new theory of consciousness that undercut this interpretation. It set him off on a quest to discover more about this fascinating topic and also led him to observe his own experience with immense attention. Out of My Head tells the gripping, highly personal, often surprisingly funny story of Parks's quest to discover more about this fascinating topic. It frames complex metaphysical considerations and technical laboratory experiments in terms we can all understand. Above all, it invites us to see space, time, color, smell, sounds, and sensations in an entirely new way. The world will feel more real after reading it."--